PENGAWASAN PADA BAGIAN MARKETING DI LEMBAGA KEUANGAN SYARIAH - Disfa Lidian Handayani (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Islamic financial institutions are known for their intermediary function that bring together surplus  parties and deficit funds. The products of sharia financial institutions require the marketing department to reach the public. In doing its activities, the marketing department must understand the concept of oversight, both by God and from the company where he works. paper Thiswill explain the concept of supervision in the field of marketing in Islamic financial institutions. paper Thiswill also discuss the monitoring in the perspective of Islam, marketing in Islamic perspective and discuss supervision in the field of marketing